PILIHAN SEKOLAH ATAU BEKERJA: ANALISIS PADA ANAK USIA SEKOLAH MENENGAH PERTAMA DI INDONESIA - Agung, Kurniawan; Pratomo, Devanto Sastha (Journal of Development Economic and Social Studies, 2022)
Child labor is a fairly common problem, and is often found to have a negative impact on school participation and violate existing laws. The purpose of this study was to examine the extent to which school or work choices for junior high school age children, the influencing factors, and the impact of poverty on these choices. This study uses data from the 2015 Intercensus Population Survey (SUPAS), using the multinomial logit method, this study focuses on children in the age range of 12-16 years in Indonesia. In this study, poverty are proxied into the variables of home ownership status, main source of lighting, and education of the head of the household (HH), it is found that children's chances of choosing school are 48 times higher than children's chances of choosing work. The results of the study state that the factors that encourage children to choose schools are gender, Indonesian language skills, home ownership of household heads, electricity as sources of lighting, household head education, and household heads who work in the service sector. While the factors that encourage children to choose to work are the age of the child, and the head of household who works in the agricultural sector. In addition, the results of the study show that children living in households with poverty are more likely to choose work, while the tendency to choose school is lower than children living in normal households.